Discovery Learning and Scientific Literacy: Integrating PISA Indicators in High School Science - Welyta Welyta; Mark Gil Vega (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The aim of this study is to analyze the level of scientific literacy among Grade X students, identify problems during the learning process, and explore factors influencing the effectiveness of Discovery Learning in teaching environmental change topics within the Merdeka Belajar curriculum framework. Methodology: This study used a mixed methods approach with a sequential explanatory design. Data were collected using multiple-choice science literacy tests, interviews with a biology teacher, and documentation. Analysis was conducted with qualitative descriptive methods. Tools included printed tests, interview guides, and documentation logs. Data validation employed triangulation of methods and sources. Main Findings: This study found that the scientific literacy of tenth-grade students at State Senior High School 1 Kota Agung was relatively low, with an average achievement of only 48%. The weakest indicator was the use of scientific evidence (15%), followed by the identification of scientific problems (17%), and the explanation of scientific phenomena (31%). Low literacy was caused by limited learning time, lack of student focus, and a suboptimal learning approach. The Discovery Learning model has the potential to increase students' active participation, conceptual understanding, and critical thinking skills. Novelty/Originality of this study: This study offers a new perspective by integrating the Discovery Learning model with PISA-based scientific literacy indicators in the context of the Merdeka Belajar curriculum. It provides empirical evidence on students’ low scientific literacy in senior high school and identifies key instructional and contextual factors, contributing to more targeted strategies for improving science education in Indonesia.